The Italian Validation of the Anosognosia Questionnaire for Dementia in Alzheimer's Disease. (September 2015) - Gambina, G.; Valbusa, V.; Corsi, N.; Ferrari, F.; Sala, F.; Broggio, E.; Condoleo, M. T.; Surdo, V.; Errera, P.; Cagnin, A. C.; Moretto, G.; Moro, V.
Although the Anosognosia Questionnaire-Dementia (AQ-D) is one of the main instruments for assessing awareness in Alzheimer's disease (AD), the normative data were until now limited to people from Argentina and Japan. This study aims to validate this instrument in an European context, in particular in an Italian sample. In a multicenter project (Verona, Padova, and Trapani), 130 patients with AD and their caregivers participated in the study. Psychometric characteristics of AQ-D are confirmed indicating that the scale permits the early identification of anosognosia and the correct care management of patients. Indeed, anosognosia results to be present also in patients with very mild AD (moderate: 44.44%; mild: 47.17%; and very mild: 23.73%). Moreover, the results indicate that deficits in awareness may vary in severity and that different types of anosognosia may be identified.